THE RELATIONSHIP BETWEEN GATRA MASTERY AND COMPOUND SENTENCE WRITING ABILITY BY CLASS VII STUDENTS OF SMP NEGERI 2 SIBORONGBORONG IN 2016/2017 ACADEMIC YEAR - DEWI IKE ANDRIANI (JURNAL ILMIAH SIMANTEK, 2020)
One of the branches of grammar is morphology, which means the science of language that discusses or studies theintricacies of word structure, as well as the effects of changes in the structure of the word on groups and their meanings. Inmorphology we will encounter morphological processes. What is meant by the morphological process is the process offorming words from their basic forms. In Indonesian, there are three most important morphological processes, namely: affixformation (affixation), repetition process (reduplication), and compounding process (composites). With the efforts that havebeen made by the Center for Language Development and Development, such as holding language seminars andcongresses, publishing various language and literary magazines, books related to language and caring for IndonesianLanguage Development programs through television, and RRI. This proves that in fact the problem of language is a problemthat concerns the interests of all the people who use it. Therefore, standardization and language development is not only theresponsibility of language experts / experts, but also all levels of society who use it. In other words, all levels of society mustbe able to take responsibility for the development of the Indonesian language. The problem of teaching Indonesian languageand literature in educational institutions should receive great attention, because the objectives of teaching Indonesian areclosely related to the process of teaching the language itself. How the success of the teaching process will be proven fromthe teaching results (output). Likewise, standard Indonesian language teaching can be achieved, if the patterns of delivery tostudents are mastered, both the standardization of sentence structures and the use of vocabulary.